Cholesterol Transport through Lysosome-Peroxisome Membrane Contacts - Chu, Bei-Bei; Liao, Ya-Cheng; Qi, Wei; Xie, Chang; Du, Ximing; Wang, Jiang; Yang, Hongyuan; Miao, Hong-Hua; Li, Bo-Liang; Song, Bao-Liang (Cell, 2015)
Cholesterol is dynamically transported among organelles, which is essential for multiple cellular functions. However, the mechanism underlying intracellular cholesterol transport has remained largely unknown. We established an amphotericin B-based assay enabling a genome-wide shRNA screen for delayed LDL-cholesterol transport and identified 341 hits with particular enrichment of peroxisome genes, suggesting a previously unappreciated pathway for cholesterol transport. We show dynamic membrane contacts between peroxisome and lysosome, which are mediated by lysosomal Synaptotagmin VII binding to the lipid PI(4,5)P2 on peroxisomal membrane. LDL-cholesterol enhances such contacts, and cholesterol is transported from lysosome to peroxisome. Disruption of critical peroxisome genes leads to cholesterol accumulation in lysosome. Together, these findings reveal an unexpected role of peroxisome in intracellular cholesterol transport. We further demonstrate massive cholesterol accumulation in human patient cells and mouse model of peroxisomal disorders, suggesting a contribution of abnormal cholesterol accumulation to these diseases. [Display omitted] •Genome-wide RNAi screen reveals 341 genes important for cholesterol transport•Lysosomal Syt7 binds peroxisomal PI(4,5)P2 to bridge the organelle contact•Organelle contacts mediate cholesterol transport from lysosome to peroxisome•Cholesterol is accumulated in cells and animal models of peroxisomal disorders Lysosome forms dynamic membrane contacts with peroxisome, and cholesterol is transported from lysosome to peroxisome. Massive cholesterol accumulates in the cells from patients with peroxisomal disorders.